LONGTERM RETENTION RATE OF CERTOLIZUMAB PEGOL IN AXIAL SPONDYLOARTHRITIS IS HIGHER: DATA FROM TURKBIO - Koca, S. S.; Pehlivan, Y.; Akar, S.; Senel, S.; Guler, A. Avanoglu; Sosyal, O.; Onen, F. (Elsevier, 2021)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 02-05, 2021 -- ELECTR NETWORK